Gastrodia madagascariensis (Gastrodieae, Orchidaceae): from an historical designation to a description of a new species from Madagascar - Martos, Florent; Johnson, Steven D; Bytebier, Benny (Phytotaxa, 2015)
Gastrodia madagascariensis, a leafless achlorophyllous orchid, is described and illustrated here. The epithet was originally coined by Perrier de la Bâthie in 1939 for fruiting material found on the eastern coastal plain of Madagascar more than a century ago, but the name was never validly published. This new species is closely related to G. similis from Reunion Island, from which it can be distinguished by the perianth tube spreading towards the apex, the shape of the column and stigma, and the flower colour. The achlorophyllous genus Gastrodia currently comprises five species in the tropical parts of the Afro-Madagascan region, one of which, G. africana, is possibly extinct. We provide an artificial key to distinguish them. In addition, there is also an extratropical species in continental Africa, the introduced G. sesamoides (very local near Cape Town, South Africa).